The Effect of Color Filters on the Visual Acuity and Contrast Sensitivity in Low Vision Patients - M Mahjoob, (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Low vision is defined as, distance visual acuity in the better eye is 20/200 or less or visual field in better eye is less than 20 degree. In this patient contrast sensitivity decreased. The use of colored filter for improve the visual function is challenge. The purpose of this study is the evaluation of visual acuity and contrast sensitivity in the low vision with and without colored filters. METHODS: In this case- control study with random sampling method 40 patients of low vision that had visual acuity 20/200 or less referred to Al Zahra ophthalmology center of Zahedan, Iran and then was categorized to 4 groups of glaucoma, diabetic retinopathy, high myopia and albinismus. Forty normal people as control group were selected. After corrected refractive error, visual acuity and contrast sensitivity was evaluated with snellen chart and Cambridge low contrast grating chart without and with red and yellow filters.FINDINGS: We found there was not significant difference between visual acuity in these 4 groups but contrast sensitivity was difference (p=0.017). Mean of contrast sensitivity in low vision patients without filter and with yellow and red filter was 19.28±20.3, 11.75±14.4 and 12.6±15.14, respectively. Paired test was shown contrast sensitivity decrease with red and yellow filter rather than without filter in 4 groups and control group (p<0.0001) while there was not significantly difference between visual acuity with and without colored filter. CONCLUSION: Contrast sensitivity evaluates the visual performance better than visual acuity in low vision. Contrast sensitivity showed that Colored filter overlays are unlikely to provide a clinically significant improvement in the visual function of low vision patients.